Insulin Sensitivity Measured with the Oral Minimal Model is lower in Obese Subjects Who Report omitting their Breakfast - JF, Brun; C, Delbos; F, Gimet; E, Raynaud de Mauverger; J, Mercier (Integrative Diabetes and Cardiovascular Diseases, 2019)
Introduction: Omitting the breakfast has been reported to promote weight gain and to impair insulin sensitivity. However this latter effect was only assessed with simple surrogates. We thus aimed at verifying if insulin sensitivity is lowered in individuals who omit their breakfast with a more quantitative assessment, using the “Oral Minimal Model” (OMM) i.e., an extension of Bergman’s minimal model to oral glucose tolerance-tests, in a cross-sectional study of a population exhibiting the full range of body mass indices.Materials and methods: We selected on our database of patients, explored for weight and/or eating disorders, 27 individuals omitting their breakfast (defined on the basis of an alimentary standardized questionnaire) and compared them to 103 matched subjects taking a hyperglucidic breakfast. The breakfast was analyzed with the OMM for the assessment of insulin sensitivity. Insulin secretion was assessed with a previously reported procedure, allowing the calculation of the parameters of phase 1 and 2 of insulin secretion of Cobelli and Mari’s models. In addition, it is already known that Mari’s model provides an index of post stimulatory potentiation of insulin secretion. Disposition indices (product of SI and insulin secretion parameters) were also determined.Results: In the 27 subjects omitting their breakfast compared to the 103 matched subjects the difference in insulin sensitivity was not found. No difference in insulin secretion parameters is detected. Homeostasis between insulin secretion and insulin sensitivity appears to be functional. However when splitting the sample in categories of BMI the expected difference appears in the range 30-40. In this subgroup (Omitting (n=9) BMI: 35.4±0.99 vs. non-omitting (n=47) BMI: 34.1±0.37 kg/m²) insulin sensitivity was lower in individuals omitting their breakfast (4.32 10-4 min-1/(μU/ml)± 0.94 vs. 9.33±1.84, p=0.03). Despite a slight increase in insulin levels and in the overall insulin secretion rate, a decrease in potentiation and in disposition index was evidenced in individuals omitting their breakfast. The lowering effect of omitting the breakfast on insulin sensitivity is thus evidenced in obese subjects in this sample (but not in those with a BMI below 30). This impairment in insulin sensitivity resulted in a decrease of glucose tolerance by 34%. This finding, based on a cross-sectional study but using a sophisticated measurement, is in agreement with the previous report that omission of the breakfast may induce resistance to insulin. It suggests that the worsening effect on SI that was experimentally found in an interventional study in healthy women becomes important enough in obese subjects to be detected in a cross-sectional study, and that this effect associates a decrease in SI and an incomplete adaptation of insulin release to this reduction in SI, and thus a decrease in glucose tolerance.